2009
DOI: 10.1080/02770900802492053
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Caregivers' Depressive Symptoms and Asthma Beliefs on Asthma Outcomes Among Low-income Puerto Rican Children

Abstract: OBJECTIVE-To examine the relationship between depressive symptoms and asthma beliefs (self efficacy and empowerment), child asthma outcomes, and caregiver's quality of life among Puerto Rican caregivers of children with asthma. METHODS-The caregivers of 221 children with persistent bronchial asthma were stratified into those with no/low or high levels of depressive symptoms. Differences between the groups in caregiver self-efficacy, family empowerment, child asthma outcomes and quality of life were examined.RE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(40 citation statements)
references
References 61 publications
3
37
0
Order By: Relevance
“…Ethnic differences in caregiver QoL related to childhood asthma exist. Lower levels of Latino caregiver QoL have been associated with more depression symptoms, decreased child QoL, poor asthma control and greater ED utilization [15][16][17]. A reciprocal relationship between QoL and asthma morbidity likely exists; so that a child's asthma morbidity will be influenced by a caregiver's current QoL and vice versa.…”
Section: Introductionmentioning
confidence: 94%
“…Ethnic differences in caregiver QoL related to childhood asthma exist. Lower levels of Latino caregiver QoL have been associated with more depression symptoms, decreased child QoL, poor asthma control and greater ED utilization [15][16][17]. A reciprocal relationship between QoL and asthma morbidity likely exists; so that a child's asthma morbidity will be influenced by a caregiver's current QoL and vice versa.…”
Section: Introductionmentioning
confidence: 94%
“…Physicians may naturally be more likely to appreciate the role of maternal psychological distress when adolescent health is poorer, but these findings suggest that psychological distress in mothers plays a key role across the range of adolescent general health. Intervention studies screening for maternal psychological distress and providing brief accessible psychological interventions [35] are needed to determine if this can lower health service use and improve adherence with treatment protocols in children and adolescents with asthma [11,17,36].…”
Section: Discussionmentioning
confidence: 99%
“…Symptoms of maternal psychological distress, including depression, are associated with poor medical adherence and disease control, as well as increased asthma morbidity [15][16][17] and in turn, increased direct and indirect health service costs [18,19]. This is particularly problematic given that children and adolescents with poorly controlled asthma account for a disproportionately large amount of health service costs [19].…”
Section: Introductionmentioning
confidence: 98%
“…In contrast, asthma management self-efficacy is negatively influenced by parent's perception of the difficulty in asthma management tasks (Morawska et al, 2008) and parental depressive symptoms (Martinez et al, 2009). No study was found that investigated the influence of child-related factors and parent asthma management self-efficacy, yet these factors (such as child age or asthma severity) are likely to be important for several reasons.…”
Section: Introductionmentioning
confidence: 93%